PENGARUH RASIO AKTIVITAS, PROFITABILITAS, LEVERAGE, ARUS KAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KONDISI FINANCIAL DISTRESS - Ni Luh Putu Widhiastuti; Ni Luh Gde Novitasari; Komang Sri Nidya Narastuti (Faculty of Economics and Business, Universitas Warmadewa, 2023)
This study aims to test and obtain empirical evidence of the effect of acticity ratio, profitability, leverage, cash flow, and company growth on financial distress condition at the manufacture companies listed in Indonesia Stock Exchange period 2018-2020. The population in this study is the manufacture companies listed in Indonesia Stock Exchange, amounting to 193 companies. The sample in this study were 87 companies based on purposive sampling technique. The analysis technique used is logistic regression analysis. The results showed that activity ratio had no effect on the financial distress, profitability had a negative effect on the financial distress, leverage had a positive effect on the financial distress, cash flow had no effect on the financial distress, and company growth had no effect on the financial distress.